Copper reduction and dioxygen activation in Cu–amyloid beta peptide complexes: insight from molecular modelling. Issue 11 (22nd October 2018) - Arrigoni, Federica; Prosdocimi, Tommaso; Mollica, Luca; De Gioia, Luca; Zampella, Giuseppe; Bertini, Luca
Abstract : Alzheimer's disease (AD) involves a number of factors including an anomalous interaction of copper with the amyloid peptide (Aβ), inducing oxidative stress with radical oxygen species (ROS) production through a three-step cycle in which O2 is gradually reduced to superoxide, oxygen peroxide and finally OH radicals. Abstract : Alzheimer's disease (AD) involves a number of factors including an anomalous interaction of copper with the amyloid peptide (Aβ), inducing oxidative stress with radical oxygen species (ROS) production through a three-step cycle in which O2 is gradually reduced to superoxide, oxygen peroxide and finally OH radicals. The purpose of this work has been to investigate the reactivity of 14 different Cu(ii )–Aβ coordination models with the aim of identifying on an energy basis (Density Functional Theory (DFT) and classical Molecular Dynamics (MD)) the redox competent form(s). Accordingly, we have specifically focused on the first three steps of the cycle, i.e. ascorbate binding to Cu(ii ), Cu(ii ) → Cu(i ) reduction and O2 reduction to O2 − . Compared to the recent literature, our results broaden the set of possible redox competent metallopeptide forms responsible for ROS production. Indeed, in addition to the three-coordinated species containing one His ligand, a N-terminal amine group and the carboxylate side chain of the Asp1 residue of Aβ already proposed, we found two other Cu–Aβ coordination modes involving two histidines.